End-stage Renal Disease After Hypertensive Disorders in Pregnancy. Issue 2 (June 2015) - Wu, C.C.; Chen, S.H.; Ho, C.H.; Liang, F.W.; Chu, C.C.; Wang, H.Y.; Lu, Y.H.
Abstract : ( Am J Obstet Gynecol 2014; 210(5):147.e1–147.e8)